Immunomodulatory properties of nanostructured systems for cancer therapy - Comparetti, Edson J.; Ferreira, Natalia N.; Ferreira, Leonardo M. B.; Kaneno, Ramon [UNESP]; Zucolotto, Valtencir (Wiley, 2022)
Based on statistical data reported in 2020, cancer was responsible for approximately 10 million deaths. Furthermore, 17 million new cases were diagnosed worldwide. Nanomedicine and immunotherapy have shown satisfactory clinical results among all scientific and technological alternatives for the treatment of cancer patients. Immunotherapy-based treatments comprise the consideration of new alternatives to hinder neoplastic proliferation and to reduce adverse events in the body, thereby promoting immune destruction of diseased cells. Additionally, nanostructured systems have been proven to elicit specific immune responses that may enhance anti-tumor activity. A new generation of nanomedicines, based on biomimetic and bioinspired systems, has been proposed to target tumors by providing immunomodulatory features and by enabling recovery of human immune destruction capacity against cancer cells. This review provides an overview of the aspects and the mechanisms by which nanomedicines can be used to enhance clinical procedures using the immune modulatory responses of nanoparticles (NPs) in the host defense system. We initially outline the cancer statistics for conventional and new treatment approaches providing a brief description of the human host defense system and basic principles of NP interactions with monocytes, leukocytes, and dendritic cells for the modulation of antitumor immune responses. A report on different biomimetic and bioinspired systems is also presented here and their particularities in cancer treatments are addressed, highlighting their immunomodulatory properties. Finally, we propose future perspectives regarding this new therapeutic strategy, highlighting the main challenges for future use in clinical practice.